Review on techniques and file formats of image compression - Alaa Jabbar Qasim; Roshidi Din; Farah Qasim Ahmed Alyousuf (Institute of Advanced Engineering and Science, 2020)
This paper presents a review of the compression technique in digital image processing. As well as a brief description of the main technologies and traditional format that commonly used in image compression. It can be defined as image compression a set of techniques that are applied to the images to store or transfer them in an effective way. In addition, this paper presents formats that use to reduce redundant information in an image, unnecessary pixels and non-visual redundancy. The conclusion of this paper The results for this paper concludes that image compression is a critical issue in digital image processing because it allows us to store or transmit image data efficiently.